Metagenomic Analysis of Saliva Reveals Disease-Associated Microbiotas in Patients With Periodontitis and Crohn’s Disease-Associated Periodontitis - Sun, Boyang; Liu, Bingyao; Gao, Xiaojiao; Xing, Kai; Xie, Li; Guo, Ting (Frontiers in Cellular and Infection Microbiology, 2021)
Patients with Crohn’s disease frequently develop oral health problems and show a higher prevalence of oral manifestations, such as dental caries and periodontitis, than healthy individuals do. In this study, a metagenomic analysis was carried out to characterize the salivary microbiota in patients with either periodontitis or Crohn’s disease-associated periodontitis. Saliva samples were collected from six patients with both Crohn’s disease and periodontitis (Cm group), six patients with periodontitis alone (Pm group), and six healthy individuals (Hm group). Genomic DNA was collected from these samples for high-throughput Illumina HiSeq metagenomic sequencing. The composition of the bacterial communities and their metabolic pathways and gene functions were characterized and compared among the three study groups. The salivary microbial communities were significantly different among the three groups, with Firmicutes, Actinobacteria, and Bacteroidetes showing the most significant differences. The Cm and Pm groups had higher abundances of Bacteroides fragilis, Prevotella baroniae, Prevotella enoeca, and Prevotella dentasini than the Hm group. The Cm and Pm groups also showed differences in their salivary microbial communities, in that the Cm group had relatively high abundances of Firmicutes and Proteobacteria, whereas the Pm group had relatively high abundances of Actinobacteria, Bacteroidetes, and Fusobacteria. In total, 34 Pm-associated (e.g., Fusobacteria and Corynebacterium matruchotii), 18 Cm-associated (e.g., Capnocytophaga and Streptococcus oralis), and 18 Hm-associated (e.g., Streptococcus and Bacillales) predominant microbial species were identified. Most genes were involved in carbohydrate and amino acid metabolism, with those of the Cm and Pm groups showing more similarity to one another but significant differences from those of the Hm group. Most of the antibiotic resistance genes were found in the Pm group. In conclusion, the salivary microbial community structure and abundance were distinct among patients with Crohn’s disease-associated periodontitis, patients with periodontitis, and healthy individuals. Further studies are needed to evaluate the potential value of these microbiota and microbiome differences in the clinical diagnosis and treatment of oral diseases.